2020
DOI: 10.3390/ijerph18010217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Non-Pharmaceutical Interventions and the Implications for Human Rights

Abstract: In response to the COVID-19 pandemic, many governments swiftly decided to order nationwide lockdowns based on limited evidence that such extreme measures were effective in containing the epidemic. A growing concern is that governments were given little time to adopt effective and proportional interventions protecting citizens’ lives while observing their freedom and rights. This paper examines the effectiveness of non-pharmaceutical interventions (NPIs) in containing COVID-19, by conducting a linear regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 27 publications
0
30
1
Order By: Relevance
“…Our results do not corroborate the findings of former studies with less countries relying on first wave data, and following different, mostly DiD type analytical approaches on school closures [10,13,[17][18][19], workplace closures [17][18][19], stay at home orders [16,18], restrictions on international travel [15], and mask obligations [11,15]. These differences may also emerge from underreporting and missing timeliness of reporting of fatalities during the first viral outbreak [14,17].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results do not corroborate the findings of former studies with less countries relying on first wave data, and following different, mostly DiD type analytical approaches on school closures [10,13,[17][18][19], workplace closures [17][18][19], stay at home orders [16,18], restrictions on international travel [15], and mask obligations [11,15]. These differences may also emerge from underreporting and missing timeliness of reporting of fatalities during the first viral outbreak [14,17].…”
Section: Discussioncontrasting
confidence: 99%
“…Fifth, we checked if our results depend on treatment timing. It is reasonable to assume that the implementation of NPIs in an early phase of the viral outbreak is more effective [19,43]. We therefore re-estimated our models separately for early and late adopters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Being a novel disease, the absence of an effective treatment and initial absence of a vaccines led sustained transmission causing huge socio-economic and health impact, necessitating countries to institute Non-Pharmaceutical Interventions (NPIs) such as hand hygiene, compulsory use of face masks, surface and object cleaning, quarantine, isolation, lock down, travel ban and restrictions [11][12][13][14][15]. Studies found a relationship between non-pharmaceutical interventions and decreased COVID-19 related mortality and morbidity in China, Europe and other part of the world [15][16][17][18][19][20]. There is evidence that people actively evaluate the NPIs using criteria such as perceived necessity, efficacy, acceptability, and feasibility [21].…”
Section: Introductionmentioning
confidence: 99%